The eyewitness - Leather, Stephen (London : Coronet Books, 2003)
Years in Yugoslavia's killing fields have desensitized Jack Solomon to the horrors of war. Working in the fractured remains of the country, he identifies victims of ethnic cleansing and tells their families. But when a truck with 26 bodies is pulled from a lake, he can't walk away from the case.
Keywords: Genocide -- Yugoslavia -- Fiction; Thrillers (Fiction)